Is Artificial Intelligence Threatening Our Self-Continuity? - González-Jiménez, Héctor (2023)
González-Jiménez, H., Pinto, D. C., Wagner, R. L., & Akdim, K. (2023). Is Artificial Intelligence Threatening Our Self-Continuity? A Temporal Appraisal and Feeling Economy Perspective [abstract]. In 2023 Global Marketing Conference at Seoul (2023): Marketing & Management Transformation in the Challenging Digital Environment (pp. 941). Global Alliance of Marketing & Management Associations. https://doi.org/10.15444/GMC2023.11.10.03